Uso de lactosuero en la formulación de helados de crema con sabor a ron pasas en el cantón Santo Domingo - Huertas Castro, Diana Eulalia (2012)
This research center aims to use whey in making ice cream flavored with rum raisins, besides looking for the right combination of raw materials to obtain a good result sensory and gain acceptance of this product. This research work was conducted in the Parish Calazacón Abraham. Coop. Villa Florida, October 9 Barrio Puerto Limon. Canton Santo Domingo, Santo Domingo Province of Tsáchilas. .....